Grain Size Analysis and Elemental Composition of the PM10 and PM5 Fractions of Gold-Tailings - Ojelede, M.E.; Annegarn, H.J.; Mlondo, M. (Mine Closure 2008: Proceedings of the Third International Seminar on Mine Closure, 2008)
Gold mine tailings deposits extend for approximately 110 km along the east-west mining corridor of the Witwatersrand. For residents living near uncovered tailings, dust-storm episodes, with high particulate loadings, are a perennial problem, especially during the austral spring. The prevalence of high wind speeds and low rainfall during August and September exacerbate the erosion of exposed tailings surfaces. Once considered only as a nuisance, the right to an environment not harmful to human health is enshrined in the Constitution of South Africa (Act 108 of 1996). A new Air Quality Management Act (No. 39 of 2004) has raised awareness regarding the health implications of the respirable and thoracic fractions of quartz-silica dust. Grain size distributions, and the elemental composition of the wind-suspendable fractions of these mine tailings, have not been reported previously. In this study, a suite of six bulk samples were selected from a sample bank of 40 collected from deposits ranging from Carltonville to Springs. Size class distributions were carried out in the diameter range 0.05 µm to 754 µm using a Malvern MS-14 Particle Analyzer with 64 channels, from which the respirable (dp < 5 µm) and thoracic (dp < 10 µm) components were calculated. Making use of a different method, tailings were screened for the respirable and thoracic mass (weight percentage), in order to validate the Malvern measurements and to obtain size class samples for chemical elemental analysis. This study appraised health-relevant particulates (respirable and thoracic) present in tailings, assessed elemental affinity for particle size and validates results obtained with the Malvern Particle Analyzer. Results from the size fractions dp < 10 µm and dp < 5 µm (range) accounted for 25 ± 7 (15 – 35) and 15 ± 4 (9 – 20) of the volume percentage. For the screening analysis, results show that the mean masses of particles in the dp <10 µm and dp < 5 µm ranges are 19 ± 8 (11 – 33) and 15 ± 4 (9 – 19) weight percentage respectively. These findings will serve as input data for qualitative human exposure and risk evaluations associated with wind-blown dust from active and closed gold mine tailings.